2015
DOI: 10.1007/s12603-014-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of iodine intake inadequacy in elderly Brazilian women. A cross-sectional study

Abstract: Background/Objectives: Inadequate iodine intake is still a problem in various regions of the world, and limited data exist regarding the ingestion of iodine in elderly people. We investigated the prevalence of iodine intake inadequacy in a group of elderly women living in a region of Brazil considered to be iodinesufficient. Design and setting: Cross-sectional study conducted in the public healthcare system of Bauru, São Paulo, Brazil. Methods: We evaluated 135 elderly women (average age of 68.2 years) who par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Nevertheless, by analysing only the subsample indicative of a stable trait on iodine consumption, this study partly overcomes the measurement error resulting from self-rated dietary information known to be sub-optimally associated with iodine sufficiency. The cohort reported rather homogeneous, high iodine intake compared to that of younger British women (6), and contemporaries in Brazil (21).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, by analysing only the subsample indicative of a stable trait on iodine consumption, this study partly overcomes the measurement error resulting from self-rated dietary information known to be sub-optimally associated with iodine sufficiency. The cohort reported rather homogeneous, high iodine intake compared to that of younger British women (6), and contemporaries in Brazil (21).…”
Section: Discussionmentioning
confidence: 79%
“…While the critical role of nutrition is becoming better understood at important developmental stages, limited data exist on iodine intake in the elderly (21), and much less is known regarding its impact throughout the lifespan. With the assumption that extreme, or very specific, consumption patterns are likely to remain relatively stable throughout life; that is, that dairy or fish avoiders in later life will have been likely to have acquired such specific dietary habits earlier in life, we identified four groups with contrasting intake of iodine-rich products in a well characterised large birth cohort of elderly adults.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported only two women with hyperthyroidism with an average intake of 154 μg/day, indicating an intake above the RDA. It is vital to identify inadequate intake in a vulnerable group such as older people to prevent disease or complications of chronic diseases in this population (DESTEFANI et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary iodine deficiency is a public health problem in many countries, especially in vulnerable groups such as older people (DESTEFANI et al, 2015). Iodine is an important micronutrient at all stages of life and is essential for thyroid hormone synthesis, brain development, and central nervous system function (MEZZOMO;NADAL, 2016;REIS et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…12 No Brasil, a maior parte dos estudos sobre esse tema foi conduzida em diferentes municípios e estados brasileiros e avaliou o estado nutricional de iodo de escolares [13][14][15] bem como a relação dos estados nutricionais de iodo encontrados nessa população com teor de iodo no sal consumido. [16][17][18] Ainda há poucos estudos brasileiros sobre o estado nutricional de iodo de gestantes e lactantes [19][20][21][22][23] , adultos e idosos [24][25][26][27] , bem como a relação dos estados nutricionais de iodo desses diferentes grupos populacionais com fatores socioeconômicos, localização do domicílio (zona urbana ou rural), classificação étnico-racial, estado nutricional (de acordo com índice de massa corporal), tabagismo, e consumo de alimentos bociogênicos. Visto isso, a realização de trabalhos como esse visa contribuir para melhor caracterização do estado de iodo de uma população em diferentes estágios de vida e colaborar no planejamento de ações em saúde pública que objetivem a prevenção, controle e/ou reversão dos DDI.…”
Section: Introductionunclassified